Identifikasi Penyebab Anak Putus Sekolah Menengah Atas atau Sederajat di Kecamatan Palolo Kabupaten Sigi - Laikun, Magfira; Zumrotin'Nisa (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This study aims to describe the factors that cause children to drop out of high school/equivalent in Palolo District, Sigi Regency. The method used is qualitative, with 21 research subjects. Data collection techniques by observation, interviews, and documentation. The research instrument used is interview guidelines. The data analysis used is descriptive qualitative. The results showed that; The results of the study can be concluded as follows: Factors in children come from themselves, namely the child's lack of interest in going to school or continuing school. Children in compulsory education age should be eager to seek knowledge but because they have been affected by an unfavorable environment for the development of children's education, children's interest in going to school does not receive proper attention, as for what causes children to be less interested in going to school: attention from parents, especially about education, also because of the lack of educated people so that most of the people who did not go to school affect children so that children's interest in school is very less. The economic condition of parents, and the low economy parents can affect their children's education, and the inability of parents to meet the educational needs of their children will have an impact on the continuity of children's education. So the economic hardship factor should not be a reason to despair. The environmental condition where the child lives is one of the factors that influence the occurrence of learning/educational activities and processes.